Establishing the role of detoxifying enzymes in field‐evolved resistance to various insecticides in the brown planthopper (Nilaparvata lugens) in South India. (25th November 2015) - Malathi, Vijayakumar Maheshwari; Jalali, Sushil K.; Gowda, Dandinashivara K. Sidde; Mohan, Muthugounder; Venkatesan, Thiruvengadam
Abstract: The brown planthopper (BPH), Nilaparvata lugens (Stål), is one of the major pests of rice throughout Asia. Extensive use of insecticides for suppressing N. lugens has resulted in the development of insecticide resistance leading to frequent control failures in the field. The aim of the present study was to evaluate resistance in the field populations of N. lugens from major rice growing states of South India to various insecticides. We also determined the activity of detoxifying enzymes (esterases [ESTs], glutathione S ‐transferases [GSTs], and mixed‐function oxidases [MFOs]). Moderate levels of resistance were detected in the field populations to acephate, thiamethoxam and buprofezin (resistance factors 1.05–20.92 fold, 4.52–14.99 fold, and 1.00–18.09 fold, respectively) as compared with susceptible strain while there were low levels of resistance to imidacloprid (resistance factor 1.23–6.70 fold) and complete sensitivity to etofenoprox (resistance factor 1.05–1.66 fold). EST activities in the field populations were 1.06 to 3.09 times higher than the susceptible strain while for GST and MFO the ratios varied from 1.29 to 3.41 and 1.03 to 1.76, respectively. The EST activity was found to be correlated to acephate resistance ( r = 0.999, P ≥ 0.001). The high selection pressure of organophosphate, neonicotinoid, and insect growth regulator (IGR) in the field is likely to be contributing for resistance in BPH to multiple insecticides, leading to control failures. The results obtained will be beneficial to IPM recommendations for the use of effective insecticides against BPH.